Consciousness, 4E cognition and Aristotle: a few conceptual and historical aspects - Stanciu, Diana (Frontiers in Computational Neuroscience, 2023)
The new approach in cognitive science largely known as '4E cognition' (embodied/ embedded/ enactive/ extended cognition), which sheds new light on the complex dynamics of human consciousness, seems to revive some of Aristotle's views. For instance, the concept of 'nature' (phusis) and the discussion on 'active intellect' (nous poiêtikos) may be particularly relevant in this respect. Out of the various definitions of 'nature' in Aristotle's Physics, On the Parts of Animals and Second Analytics, I will concentrate on nature defined as an inner impulse to movement, neither entirely 'corporeal', nor entirely 'incorporeal', neither entirely 'substantial', nor entirely 'accidental'. Related to that, I will consider the distinction in On the Soul between the 'active' and the 'passive' intellect, which Aristotle asserted as generally present in 'nature' itself. By offering a conceptual and historical analysis of these views, I intend to show how the mind-body problem, which is essential for the explanation of consciousness, could be somewhat either eluded or transcended by both ancients and contemporaries on the basis of a subtle account of causation. While not attempting at diminishing the impact of the Cartesian paradigm, which led to the so-called 'hard problem of consciousness', I suggest that the most recent neuroscience discoveries on the neurophysiological phenomena related to human consciousness could be better explained and understood if interpreted within a 4E cognition paradigm, inspired by some Aristotelian views.